A Qualitative Investigation of Pragmatic Development in Foreign and Target Context (GIST – Education and Learning Research Journal, 2018)
The effects of learning environment on language development in general and pragmatic competence have received increasing attention in the last few decades. The existing studies examined the effects of ESL and EFL settings on pragmatic development from a variety of standpoints. Taking these studies as the basis, this comparative case study aimed to investigate the effects of target context and foreign context on the pragmatic development of two groups of learners, one learning a foreign language (English) and the other learning a second language (Turkish). What differentiates this study from the previous ones is that it compares the cases of learning foreign and second languages (by two different student groups) in the same country (Turkey) The participants, selected on purposeful sampling, were one group of Turkish learners of English in an EFL department in Turkey and the other group was learners from different nationalities learning Turkish in Turkey. The data were collected through participants’ self-reports, interviews and in-class observations by the researcher. The content analysis mainly revealed that the foreign context did not offer learners adequate chances for exposure to and practice in the target language, which negatively influenced their pragmatic development. However, the target context provided ample chances of natural and authentic communication in which learners of Turkish could develop their pragmatic knowledge and production. Based on these results, some pedagogical and practical suggestions are provided.
Keywords: pragmatic competence; foreign language context; second language context